Analysis of an Existing Box Culvert Structure with or Without Retrofiting Using Analysis Tool - Akshay Joshi; Rahul Kumar Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2025)
The design and comparative analysis of box culverts subjected to vehicle loading are the main topics of this study. For the structural analysis and design of an old and a retrofitted culvert, STAAD Pro CONNECT Edition was used. Using STAAD Pro, a comprehensive 3D model with geometric and material properties was made for every culvert. A comparative study of the outcomes showed that the modified culvert had greatly improved. Significant reductions in axial force, shear force, bending moment, and torsion in comparison to the original structure are among the main findings. These improvements were ascribed to the extra reinforcement that was added in the course of the retrofitting. The modified culvert showed improved stiffness, overall structural integrity, and load-carrying capability. The study demonstrates how well STAAD Pro CONNECT Edition works for box culvert design and analysis.
Keywords: box culvert; STAAD Pro CONNECT Edition; vehicular loading; structural analysis; design; retrofitting; axial force; shear force